Reaction Time and Response Inhibition in Autosomal Dominant Alzheimer’s Disease - Medina, Luis D. (Brain Cogn, 2020)
OBJECTIVE: Subtle deficits in several cognitive domains characterize the neuropsychological profile of preclinical Alzheimer’s disease (AD). Assessment of preclinical individuals with genes causing autosomal dominant AD (ADAD) provides a model for prodromal disease. We sought to sensitively evaluate attention and working memory using a computerized battery in non-demented persons carrying ADAD mutations. METHOD: A total of 71 non-demented Latinos at-risk for ADAD mutations were recruited [40 mutation carriers (MCs), 31 non-mutation carriers (NCs)] and completed a Spanish language chronometric battery of speeded decision and working memory tasks. RESULTS: On two complex reaction time (RT) tasks involving decision-making and response inhibition, MCs exhibited slower RTs than NCs as they approached their anticipated age of dementia diagnosis. Education moderated these effects, but only in younger MCs. APOE ε4 status was not associated with age-related slowing among NCs or MCs on any of the tests. CONCLUSIONS: Our findings indicate MCs respond more slowly as they approach the age of dementia onset on tasks with greater demands on executive function. Our results also suggest these effects were not explained by APOE ε4 status independently of ADAD mutation status. Computerized reaction time tests can provide sensitive measures of the earliest cognitive changes in AD.